Association of periprocedural myocardial infarction with long‐term survival in patients treated with coronary revascularization therapy of chronic total occlusion. Issue 6 (3rd November 2015) - Jang, Woo Jin; Yang, Jeong Hoon; Choi, Seung‐Hyuk; Song, Young Bin; Hahn, Joo‐Yong; Kim, Wook Sung; Lee, Young Tak; Kim, Bum‐Sung; Gwon, Hyeon‐Cheol
Abstract : Objective: To evaluate the impact of periprocedural myocardial infarction (PMI) on long‐term survival after coronary revascularization in patients with chronic total occlusion (CTO). Background: Little is known about the clinical impact of PMI on long‐term cardiac mortality after CTO revascularization in patients with stable angina. Methods: We analyzed data from 927 patients with CTO and stable angina who were treated with coronary artery bypass grafting (CABG, n  = 367) or percutaneous coronary intervention (PCI, n  = 560). PMI was defined as a peak CK‐MB ≥ 3 times the upper limit of normal (ULN) after PCI or a CK‐MB ≥ 5 times the ULN after CABG. The primary outcome was cardiac death in patients with PMI (PMI group, n  = 118 [12.7%]) or without PMI (no‐PMI group, n  = 809 [87.3%]) after revascularization. Results: During a median follow‐up of 42 months, PMI occurred in 118 patients (12.7% of the overall study population). Fifty‐nine patients treated with PCI (10.5% of PCI subgroup) and 59 patients treated with CABG (16.1% of CABG subgroup) suffered from PMI. In multivariate analysis, the PMI group and the no‐PMI group had a similar incidence of cardiac death (hazard ratio [HR] 0.57; 95% confidence interval [CI] 0.20 to 1.62; P  = 0.29). Conclusions: PMI may not be associated with increased cardiac mortality after coronary revascularization in patients with stable CTO. © 2015 Wiley Periodicals, Inc.